Analisis pengaruh fraud pentagon terhadap kecurangan laporan keuangan: Studi empiris pada perusahaan LQ45 tahun 2018-2022 - Pradana, Eduardus Henriko Putra; Suwasono, Heru (Nur Science Institute, 2024)
This research aims to determine the influence of external pressure, managerial ownership, the ineffectiveness of supervision, the nature of the industry, change of auditor, change of board of directors, and frequent number of CEO's pictures on financial statement fraud. The population in this research is all companies listed as the LQ-45 index on the Indonesia Stock Exchange (BEI) for the 2018-2022 period respectively. The sampling technique uses purposive sampling with a sample size of 105 companies. The analysis method uses multiple linear regression analysis. The research results found that managerial ownership and the nature of the industry have a positive effect on financial report fraud. Meanwhile, changing auditors hurts financial reporting fraud. Apart from that, external pressure, ineffective supervision, change of auditor, and frequent number of CEO's pictures do not affect financial statement fraud. In general, the independent variables in this research can explain fraudulent financial reports in companies listed as the LQ-45 index on the Indonesia Stock Exchange for the 2018-2022 period of 15.6 percent.